Oral narrative structure and coherence of children with attention deficit hyperactivity disorder - Zenaro, Mariana Pereira [UNESP]; Rossi, Natalia Freitas [UNESP]; de Souza, Ana Luiza Decanini Miranda [UNESP]; Giacheti, Célia Maria [UNESP] (FapUNIFESP (SciELO), 2019)
Purpose: This study aimed to characterize and compare the use of typical story grammar elements and global coherence level in the oral narrative of children with Attention Deficit Hyperactivity Disorder with the narrative of children without the disorder and with typical development. Methods: A total of 40 children of both sexes aged 5 to 10 years who attended elementary school participated in the study, 20 of whom were diagnosed with Attention Deficit Hyperactivity Disorder (ADHD Group), and 20 with typical development (TD Group). Participants from each group were similar in sex, chronological age, schooling and socioeconomic status. The wordless picture book Frog, Where Are You? was used to elicit the oral narrative analyzed for the presence of the main typical elements of the story schema (character, theme/topic, event/plot and outcome), and afterwards their narration was classified according to four different levels of organization corresponding to the global story coherence level. Results: The ADHD Group presented lower scores on the structural elements theme/ topic and outcome and a narrative with lower degree of coherence compared to the TD Group. Conclusion: The children with ADHD included in this study presented difficulties to use typical story grammar elements, mainly related to the maintenance of the central theme and outcome of the story. These elements are considered fundamental for construction of narrative coherence, which justifies the lower levels of global coherence found in the oral narrative of the ADHD Group.
Keywords: Attention deficit disorder with hyperactivity; Children's language; Developmental disabilities; Language development; Narration